Transforming Growth Factor-β Signaling Plays a Pivotal Role in the Interplay Between Osteosarcoma Cells and Their Microenvironment - Verrecchia, Franck; Rédini, Françoise (Frontiers in Oncology, 2018)
Osteosarcomas are the most frequent form of primary bone tumors and mainly affect children, adolescents and young adults. Despite encouraging progress in therapeutic management, including the advent of multidrug chemotherapy, the survival rates have remained unchanged for more than 4 decades: 75% at 5 years for localized disease, but two groups of patients are still at high risk: metastatic at diagnosis (overall survival around 40% at 5 years) and/or poor responders to chemotherapy (20% at 5 years). Because these tumors are classified as "complex genomic", it is extremely difficult to determine the signaling pathways that might be targeted by specific therapies. A hypothesis has thus emerged, stating that the particular microenvironment of these tumors may interfere with the tumor cells that promote chemoresistance and the dissemination of metastases. The stroma is composed of a large number of cell types (immune cells, endothelial cells, mesenchymal stromal cells,…) which secrete growth factors, such as Transforming Growth Factor-β (TGF-β), which favor the development of primary tumors and dissemination of metastases by constituting a permissive niche at primary and distant sites. Rather than targeting the tumor cells themselves, which are very heterogeneous in osteosarcoma, the hypothesis is instead to target the key actors secreted in the microenvironment, such as TGF-βs, which play a part in tumor progression. In the last decade, numerous studies have shown that overexpression of TGF-β is a hallmark of many cancers, including primary bone tumors. In this context, TGF-β signaling has emerged as a crucial factor in the cross-talk between tumor cells and stroma cells in poor-prognosis cancers. Secretion of TGF-β by tumor cells or stroma cells can effectively act in a paracrine manner to regulate the phenotype and functions of the microenvironment to stimulate protumorigenic microenvironmental changes. TGF-β can thus exert its protumorigenic function in primary bone tumors by promoting angiogenesis, bone remodeling and cell migration, and by inhibiting immunosurveillance. This review focuses on the involvement of TGF-β signaling in primary bone tumor development, and the related therapeutic options that may be possible for these tumors.